The impact of high plant density on dry matter remobilization and stalk lodging in maize genotypes with a different stay-green degree. Issue 4 (21st March 2021) - Shao, Hui; Shi, Dongfeng; Shi, Wenjun; Ban, Xiangben; Chen, Yachao; Ren, Wei; Chen, Fanjun; Mi, Guohua
ABSTRACT: To test the hypothesis that stay-green genotypes help to increase stalk lodging resistance under high planting density by reducing dry matter remobilization from stalk, a two-year field study with three planting densities (60, 000, 75, 000, and 90, 000 plants per ha) and six hybrids was conducted. When planting density changed from 75, 000 to 90, 000, stalk dry matter remobilization efficiency increased by 4.1–191%. Stem dry weight per length, rind penetration strength, average crushing strength for the first to fifth internode, and average bending strength for the third to fifth internode decreased by 25.4–47.2%, 5.1–24.6%, 1.4–29.9%, and 14.0–36.0%, respectively. Stalk lodging rate increased by 17–275%. Stalk dry matter remobilization efficiency was negatively correlated to either stem dry weight per length (r = 0.23, p < 0.05), rind penetration strength (r = 0.75, p < 0.01), crushing strength (r = 0.61, p < 0.01), or bending strength (r = 0.32, p < 0.01). Cultivars with higher stay-green degree (SR999, LY99, and NH101) had lower stalk lodging rate compared to the senescent cultivars XY335 and LY918. It is concluded that stay-green genotypes with low dry matter remobilization help to strengthen stem and reduce stalk lodging risk.